BUDAYA ORGANISASI DAN DISIPLIN KERJA SERTA PENGARUHNYA TERHADAP KINERJA KARYAWAN - Munawir Nasir; Rezky Ratnasari Taufan; Muhammad Fadhil; Muh Haerdiansyah Syahnur (AkMen JURNAL ILMIAH, 2021)
The purpose of this study is to determine the relationship between organizational culture and work discipline on employee performance. The research was conducted at one of the credit unions in South Sulawesi's district of Pinrang. The research design is quantitative, with statistical analysis performed using the SPSS v 25 application. The saturation sampling technique was used in this study, which included all members of the population, which amounted to 20 employees. The findings indicate that organizational culture has no effect on employee performance, as evidenced by the fact that the tvalue (1.771) is less than the ttable which (2.109). While work discipline has a positive and significant effect on performance, which shows that the tvalue (2.973) is bigger than the ttable. Simultaneous testing revealed that organizational culture and work discipline both have an effect on employee performance. The R2 value in this study was 0.701, indicating that organizational culture and work discipline variables have a combined effect on employee performance, with the remaining 70.1 percent, or 29.9 percent, influenced by variables not included in the regression equation or variables researched